Muslim World and the Globalisation Challenge: [En]Countering Dehumanization or Humanised Integration - Azhar Ibrahim (Dirosat : Journal of Islamic Studies, 2016)
Globalisation is a challenge for Muslim world as it can be opportunities. The term globalisation mostly refers to the opening up the market to transnational corporations (TNCs) which is in line with liberalisation of the economy. Ironically those who call for “opening up of borders” or “capital liberalisation” are actually the one who are so strict in the immigration policies and practices. Protecting their own labour market, while encouraging their own TNCs to optimise their presence in the developing countries is a blatant contradiction. The calamitous effects of neoliberal globalisation are striking crucial aspects of life, such as economic justice, environmental condition, and educational system. Therefore, critical response to globalisation is imperative. In many ways, the readiness to discuss critically on globalisation is very much to be welcomed. This paper points to the need to discuss beyond the preoccupation of economic needs. It proposes to create and project another kind of globalisation which points to a humanised global integration. The real opportunity is when we are able to see the problems of humankind as a whole. Muslim must be at the forefront in forging human solidarity and cooperation so as to attain a humanised global order.